PENGARUH PENGGUNAAN MEDIA E-LEARNING BERBASIS MOODLE DAN MINAT BELAJAR TERHADAP HASIL BELAJAR PRAKARYA DAN KEWIRAUSAHAAN - Khasanah Khasanah; Musa Musa (Akademika : Jurnal Teknologi Pendidikan, 2019)
The purpose of testing things as follows: 1) to know the differences in craft and entrepreneurship learning outcomes between moodle-based e-learning media using print media. 2) knowing whether there is an interaction between learning media and learning interest in craft learning outcomes and entrepreneurship. 3) craft learning and entrepreneurship results in students who are interested in learning high who use moodle-based e-learning media compared to using print media at high interest. 4) differences in craft and entrepreneurship learning outcomes that use moodle-based e-learning media and print media for low interest students. This study involved 60 samples taken by random sampling technique in the class X almuslim Tambun High School, with the instruments used were test models for learning outcomes and questionnaires for student interest, then processed with SPSS Ver 22 For Window application with ANOVA statistical analysis data processing and Tukey.